Fearless women : feminist patriots from Abigail Adams to Beyoncé - Cobbs, Elizabeth (The Belknap Press of Harvard University Press, 2023)
"Cobbs traces the long history of American feminism, dating back to the Revolution, when the founding principle of equality became a battering ram against hierarchy. She tells this story through the public and private lives of 16 women who pushed the boundaries of their times and insisted on their right to control their bodies and their lives"--